The Impact of Earnings Per Share, Dividend Payout Ratio, BI Rate, and Inflation on Stock Price Volatility - Jannati, Ayu Sufi; Hasibuan, Henny Triyana (E-Jurnal Akuntansi; Vol 35 No 2 (2025), 2025)
This research aims to provide empirical evidence on the influence of Earnings Per Share (EPS), Dividend Payout Ratio, BI Rate, and Inflation on Stock Price Volatility. The study focuses on companies listed in the Kompas 100 Index on the Indonesian Stock Exchange (IDX) during the 2018-2022 period. A total of 120 observations were obtained from 24 companies selected using the purposive sampling method, with a five-year observation period. The data analysis technique employed in this research is multiple linear regression analysis. The results indicate that Earnings Per Share and Inflation negatively affect stock price volatility, while the BI Rate has a positive effect. The Dividend Payout Ratio, however, shows no significant impact on stock price volatility. These findings support the validity of signaling theory in explaining the effects of EPS, the BI Rate, and Inflation on stock price volatility. Keywords: Earnings Per Share; Dividend Payout Ratio; BI Rate; Inflation; Stock Price Volatility